Initial Experience with 64Cu-DOTATATE Digital PET of Patients with Neuroendocrine Neoplasms: Comparison with Analog PET - Mathias Loft; Camilla B. Johnbeck; Esben A. Carlsen; Helle H. Johannesen; Peter Oturai; Seppo W. Langer; Ulrich Knigge; Andreas Kjaer (Diagnostics, 2021)
The recent introduction of solid-state detectors in clinical positron emission tomography (PET) scanners has significantly improved image quality and spatial resolution and shortened acquisition time compared to conventional analog PET scanners. In an initial evaluation of the performance of our newly acquired Siemens Biograph Vision 600 PET/CT (digital PET/CT) scanner for 64Cu-DOTATATE imaging, we compared PET/CT acquisitions from patients with neuroendocrine neoplasms (NENs) grades 1 and 2 and stable disease on CT who were scanned on both our Siemens Biograph 128 mCT PET/CT (analog PET/CT) and digital PET/CT within 6 months as part of their routine clinical management. Five patients fulfilled the criteria and were included in the analysis. The digital PET acquisition time was less than 1/3 of the analog PET acquisition time (digital PET, mean (min:s): 08:20 (range, 07:59–09:45); analog PET, 25:28 (24:39–28:44), p < 0.001). All 44 lesions detected on the analog PET with corresponding structural correlates on the CT were also found on the digital PET performed 137 (107–176) days later. Our initial findings suggest that digital 64Cu-DOTATATE PET can successfully be performed in patients with NENs using an image acquisition time of only 1/3 of what is used for an analog 64Cu-DOTATATE PET.